Relationship Level Of Knowledge, Attitude And Behavior To The Incidence Of Scabies At The Al Fatih Klaten Modern Islamic Boarding School - Melok Tin Hartini; Retno Indrastiti; Rina Purnamasari (Jurnal EduHealth, 2023)
Scabies is a skin disease that is most often found in densely populated environments such as Islamic boarding schools. This disease is caused by Sarcoptes scabiei homini. Education for students about scabies is necessary to increase awareness of hygiene behaviors. Education related to knowledge, attitudes and behavior to scabies has been carried out regularly every six months by the Dermatologist and Venereologist. This study aims to determine knowledge, attitudes and behavior to the incidence of scabies at Modern Islamic Boarding School Al Fatih, Klaten. This study used quantitative research design with a cross sectional design which was carried out in March 2023 at the Al Fatih Modern Islamic Boarding School, Klaten. The sample was 65 students were obtained by the total sampling method that met the inclusion criteria. Data obtained by direct examination and using a questionnaire. The diagnosis of scabies is made based on the criteria in the Regulation of the Ministry of Health of the Republic of Indonesia No. 5 of 2014 concerning Guidelines for Clinical Practice for Doctors in Primary Health Care Facilities. The results of the study showed that 40% of the respondents experienced scabies. Bivariate analysis with Spearman's Rank correlation test for the knowledge variable obtained p-value 0.873 where there was no significant relationship between knowledge and the incidence of scabies. As many as 40% of students who had a positive attitude were diagnosed with scabies. The relationship between behavior and the incidence of scabies was found to be p -value 0.03 where there was a significant relationship between behavior and the incidence of scabies. Amount of 40%students had a positive attitude were diagnosed with scabies. There was no significant relationship between knowledge and the incidence of scabies. However, there was a significant relationship between behavior and the incidence of scabies at the Al Fatih Modern Islamic Boarding School, Klaten Regency.